The Effect of Beeswax and Glycerol Addition on the Performance of Bioplastic Film Made of Konjac Glucomannan (Jurnal Bahan Alam Terbarukan, 2022)
In this study, bioplastics made of Konjac glucomannan have been successfully prepared via film casting method. The effects of addition of beeswax content (i.e. of 0%, 0.5%, and 1%,), as well as glycerol content (i.e. 0.5%, 1%, and 1.5%) on the properties of the bioplastics have been investigated. The bioplastics produced have been characterized for their tensile strength, percent elongation, swelling degree, and biodegradability. The results of this study, showed that most of the bioplastic samples have weight loss of about 95% after the drying process as well as the finished film. The addition of beeswax and glycerol concentrations also increased tensile strength and percent elongation of the bioplastics. The highest value of tensile strength occurred at bioplastic film with a concentration of 1.5% beeswax and 1% glycerol (i.e. Sample C3) with a value of approximately 3.5 MPa. Whereas, the highest percent elongation value occurred at bioplastic film with a concentration of 1.5% beeswax and 1% glycerol (i.e. Sample C3) with a value of approximately 23.29%. These tensile and percent elongation values were higher or comparable to other bioplastic samples made from starch of different raw materials reported by literatures. In the other hand, the addition of beeswax and glycerol decreased the degree of swelling. The degree of swelling for all the bioplastic film samples were in the range of 316.77 – 481%.